Efficient integration of personal factors into the international classification of functioning, disability, and health (ICF): the importance of emotional and motivational aspects in goal pursuit - Tsuda, Ayano; Manalo, Emmanuel; Miyai, Ichiro; Noda, Tomoyuki (Frontiers in Rehabilitation Sciences, 2024)
The International Classification of Functioning, Disability, and Health (ICF) is a widely used framework in rehabilitation that provides standardized measures to describe health and health-related states of people. The strength of the ICF lies in its provision of a common language for describing rehabilitation progress. However, personal factors are not classified within the ICF due to their significant variability across cultures, which may render it not adequately capturing the subjective and social dimensions of disability. Our objective in this research was to propose theoretical frameworks that could help identify relevant personal factors for inclusion in the ICF. We discuss the Personality Systems Interaction (PSI) Theory to identify personal variability in goal pursuit, highlighting the importance of emotions like negative and positive affect in handling adverse situations and managing habitual behaviors. Additionally, the theory helps to determine personality factors relevant to patients, facilitating the resolution of potential issues that may emerge during the goal achievement process. We also emphasize the role of goal setting in rehabilitation and suggest the Goal-Oriented Action Linking (GOAL) model as a useful tool for understanding how motivational values change over time, distance, and progress. Following from this, we discuss the importance of self-efficacy and its relationship to effort and goal achievement, while noting potential issues in its assessment. Finally, we propose viable assessment methods for measuring the potential components to be incorporated as personal factors.